Small shelly fossils from the argillaceous facies of the Lower Cambrian Forteau Formation of western Newfoundland - Skovsted, Christian B.; Peel, John S (2007)
A diverse fauna of helcionelloid molluscs, hyoliths, and other small shelly fossils is described from limestone layers within the Forteau Formation of the Bonne Bay region in western Newfoundland. The fauna is dominated by internal moulds of various molluscs and tubular problematica, but also includes hyolith opercula, echinoderm ossicles, and other calcareous small shelly fossils preserved by phosphatisation. Originally organophosphatic shells are comparatively rare, but are represented by brachiopods, hyolithelminths, and tommotiids. The fauna is similar to other late Early Cambrian faunas from slope and outer shelf settings along the eastern margin of Laurentia and may be of middle Dyeran age. The similarity of these faunas indicates that at least by the late Early Cambrian, a distinctive and laterally continuous outer shelf fauna had evolved. The Forteau Formation also shares elements with faunas from other Early Cambrian provinces, strengthening ties between Laurentia and Australia, China, and Europe during the late Early Cambrian. Two new taxa of problematic fossil organisms are described, the conical Clavitella curvata gen. et sp. nov. and the wedge-shaped Sphenopteron boomerang gen, et sp. nov.